Summer Mungbean for remunerative farming - Kumar, Ashutosh; Maurya, Ramanuj; Parihar, A. K.; Dixit, G. P.; Gupta, Sanjeev (Indian Farming, 2017)
The increasing popularity of the summer mungbean cultivation is due to new adoptable technology and recommended varieties by which pulses growing area is expanding progressively especially in the Northern India. Recommended varieties of mungbean have the ability to mature between 55 to 60 days by which the farmers can plan for summer mungbean cultivation and by spending onlyÂ Rupees 10,000.00-12,000.00/hectare can obtain Rupees 60,000 to 65,000 within two months period time. On the basis of overall mean the productivity gain through the advance package technology adoption was 48% as compared to farmersâ€™ practices.